Tumor necrosis factor inhibitors enhance corticosteroid therapy for Stevens-Johnson syndrome and toxic epidermal necrolysis linked to immune checkpoint inhibitors: a prospective study - He, Chun-Xia; Guo, Lan; Qu, Tao; Jin, Hong-Zhong (Frontiers in Immunology, 2024)
Introduction Immune-related epidermal necrolysis (irEN), including Stevens-Johnson Syndrome (SJS) and toxic epidermal necrolysis (TEN), represents a potentially lethal reaction to immune checkpoint inhibitors. An optimal treatment strategy remains undefined. This study evaluates the effectiveness and safety of combination therapy with corticosteroids and tumor necrosis factor inhibitors (TNFi) in treating irEN patients. Methods In this single-center, prospective, observational study, patients with irEN received either corticosteroid monotherapy or a combination therapy of corticosteroids and TNFi (etanercept for SJS, infliximab for TEN). The primary endpoint was re-epithelization time, with secondary endpoints including corticosteroid exposure, major adverse event incidence, acute mortality rates, and biomarkers indicating disease activity and prognosis. The study was registered at the Chinese Clinical Trial Registry (ChiCTR2100051052). Results Thirty-two patients were enrolled (21 SJS, 11 TEN); 14 received combination therapy and 18 received corticosteroid monotherapy. IrEN typically occurred after 1 cycle of ICI administration, with a median latency of 16 days. Despite higher SCORTEN scores in the combination group (3 vs. 2, p = 0.008), these patients experienced faster re-epithelization (14 vs. 21 days; p < 0.001), shorter corticosteroid treatment duration (22 vs. 32 days; p = 0.005), and lower prednisone cumulative dose (1177 mg vs. 1594 mg; p = 0.073). Major adverse event rates were similar between groups. Three deaths occurred due to lung infection or disseminated intravascular coagulation, with mortality rates for both groups lower than predicted. Potential risk factors for increased mortality included continuous reduction in lymphocyte subset counts (CD4+ T cells, CD8+ T cells, natural killer cells) and consistent rises in inflammatory markers (serum ferritin, interleukin-6, TNF-α). Re-epithelization time negatively correlated with body mass index and positively correlated with epidermal detachment area and serum levels of interleukin-6 and TNF-α. Conclusions Corticosteroids combined with TNFi markedly promote re-epithelization, reduce corticosteroid use, and decrease acute mortality in irEN patients without increasing major adverse events, offering a superior alternative to corticosteroid monotherapy. Inflammatory markers and lymphocyte subsets are valuable for assessing disease activity and prognosis.